Gonadal morphology and difference in reproductive development of two isolated populations of Astyanax rivularis (Teleostei, Characidae) - Quirino, Patricia Postingel [UNESP]; de Siqueira-Silva, Diógenes Henrique; da Silva Rodrigues, Maira [UNESP]; dos Santos-Silva, Amanda Pereira; Delgado, Maria Luiza Ribeiro [UNESP]; Senhorini, José Augusto; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (My University, 2021)
Individuals of the same species may present different reproductive tactics depending on the environment in which they develop and mature. The present study aimed to define the gonadal development phases of males and females of Astyanax rivularis and to carry out a comparative analysis of the reproductive development of specimens captured in two isolated environments of the São Francisco River basin in Serra da Canastra, Brazil (Point 1: low vegetation and river showing calm and crystalline waters with small well formations; Point 2: current waters, and well-established areas of arboreal vegetation). Thus, the gonads of A. rivularis specimens were collected, fixed and processed with techniques for light microscopy. Five maturation phases of the females' reproductive cycle were established: immature, developing, spawning capable, regressing and regenerating. Three maturation phases of the males' reproductive cycle were observed: spawning capable, regressing, and regenerating. There are differences in the phases of gonadal development of A. rivularis between the two sampling points so that, possibly, animals upstream of the waterfall demonstrate a delay in the reproductive cycle in relation to animals downstream.
Keywords: geographic isolation; oogenesis; reproduction; reproductive development; spermatogenesis